Persistent Hiccups—An Unusual Presentation of Bilateral Pheochromocytoma without Syndromic Association: A Case Report - Nitin Aherrao; Nilesh Kumar; Indarajeet Singh Gambhir; Dhiraj Kishore; Suryakumar Singh; Abhinandan Mishra; Aravind Anand (Case Reports in Endocrinology)
Pheochromocytoma is a rare catecholamine-producing tumor arising from chromaffin tissue in the adrenal medulla, occurring in less than 0.2 percent of patients with hypertension. The mean age at diagnosis is about 40 years. Pheochromocytomas are commonly inherited as features of multiple endocrine neoplasia type 2 or several other pheochromocytoma-associated syndromes and have variable clinical presentation. Among the presenting symptoms, episodes of palpitations, headaches, and profuse sweating are typical and constitute a classic triad. We report a case of a 17-year-old male patient with rare bilateral pheochromocytoma presenting with persistent hiccups for 4 months and blurring of vision for 1 week, later followed by hypertensive crisis. There was neither family history of pheochromocytoma nor any classic symptoms. Patient was diagnosed with bilateral pheochromocytoma without any syndromic association. But still this patient needs to be followed for future development of medullary carcinoma of thyroid because it could be an initial presentation of MEN 2A/2B/VHL syndromes. Our paper highlights the importance of maintaining a high level of suspicion for persistent hiccups and careful clinical screening for hypertension even in absence of associated syndromes of pheochromocytoma and classical symptoms to achieve prompt diagnosis and to avoid improper management.